Discrepancies in perception and evaluation of macroenvironment – sectoral analysis - Belas, Jaroslav; Gavurova, Beata; Kubalek, Jan; Kubak, Matus (Journal of Business Economics and Management, 2020)
The aim of presented study is to evaluate macroeconomic environment and to determine differences in perception of macroeconomic environment by entrepreneurs in Slovak Republic and Czech Republic. Data collection was done by questionnaire which was answered by 329 entrepreneurs from Slovak Republic and 312 entrepreneurs from Czech Republic. Topics treated concerning macroenvironment were the favourableness of macroenvironment for business activities, its support for starting an entrepreneurship, its support of innovation activities of companies and its capacity to promote entrepreneurship and to create interesting business opportunities. Answers are divided according to sector in which entrepreneurs doing business. Considered sectors are: transport, trade, construction, production, agriculture, services and other sectors. To analyse collected data, we use correspondence analysis. Results show that there exists systematic difference in perception of macroenvironment by entrepreneurs from SMEs in Slovak Republic and Czech Republic. It seems that entrepreneurs from Czech Republic percept macroenvironment more positively than Slovak ones. Moreover, we document different perception of macroeconomic situation depending on sector in which entrepreneurs operate. Presented research results bring findings for the creators of economic policies. Similarly, presented results form a platform for concepts of strategic and regional plans in order to provide sustainable business environment in the countries, and also their stable economic growth.